Indolence, incentives, and institutions - De Dios, Emmanuel S. ([Quezon City] School of Economics, University of the Philippines, 2011)
Rizal?s economic ideas are among the least studied aspects of his work. A careful reading of his writing, however, particularly his 1890 essay ?On the indolence of the Filipinos,? suggests that Rizal?s economic views were in general agreement with those of Enlightenment thinkers regarding the basis of progress, which was to be found in freedom of commerce and a government that was effective in its inherently limited sphere. The apparent absence of specific recommendations or hints of economic policy did not reflect a lacuna in Rizal?s thought but a proper concern for the prior and more important issues of specifying the minimal institutional foundations of a functioning economy?namely, the maintenance of peace, security of property rights, and facilitating the free movement of people and goods. Rizal went beyond Smithian minimalism, however, since he viewed the Spanish colonization as having not only severely undermined incentives but also destroyed hitherto promising and sound informal institutions that would have supported material progress among the subject Filipinos. As a result, Rizal viewed the reform of formal institutions as a necessary but insufficient condition for promoting the country?s economic progress. This was another important reason for his insistence on the need for mass education.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 76-78)
Keywords: Rizal, Jose -- 1861-1896 -- Political ans social views; Spain -- Colonies -- Philippines -- Administration; Philippines -- Economic conditions -- 19th century